THE ROLE OF TECHNOLOGY IN CREATING ENGAGING AND EFFECTIVE LANGUAGE LEARNING EXPERIENCES - Sylvia, Sylvia; Pratiwi, Yessi Anissa (TRANSFORMATIONAL LANGUAGE, LITERATURE, AND TECHNOLOGY OVERVIEW IN LEARNING, 2022)
Language instruction is one of the areas that have been radically altered by including technology into education; this has resulted in new learning instruments that maintain the attention of students and make it simple for them to learn. This work examines how technology creates effective language learning environments that are inviting to learners by focusing on the type of technologies used in such contexts as well as their effect on student involvement, encouragement, and achievement. Using mixed methods including qualitative interviews and focus groups in addition to quantitative questionnaires, this research provides a detailed analysis on how technological instruments affect language acquisition. It showed that using technology not only aids understanding with varied interactive tasks but also enables unique experiences based on personal preferences. This indicates an need for strategic integration of technology within language education if improved mastery of a language is desired along with higher student interest and better comprehension of it’s cultural contexts.